2023
DOI: 10.1007/s00018-023-04818-4
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen therapy as a potential therapeutic intervention in heart disease: from the past evidence to future application

Abstract: Cardiovascular disease is the leading cause of mortality worldwide. Excessive oxidative stress and inflammation play an important role in the development and progression of cardiovascular disease. Molecular hydrogen, a small colorless and odorless molecule, is considered harmless in daily life when its concentration is below 4% at room temperature. Owing to the small size of the hydrogen molecule, it can easily penetrate the cell membrane and can be metabolized without residue. Molecular hydrogen can be admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…H 2 has been demonstrated to possess anti-inflammatory, antioxidant, and anti-endoplasmic reticulum (ER) stress properties, and its involvement in the regulation of apoptosis, autophagy, and pyroptosis has been elucidated [12][13][14][15][16][17][18]. In this regard, H 2 can be considered a unique molecule that influences fundamental biological responses.…”
Section: Latest Insights Into H 2 Biology Research-brief Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 has been demonstrated to possess anti-inflammatory, antioxidant, and anti-endoplasmic reticulum (ER) stress properties, and its involvement in the regulation of apoptosis, autophagy, and pyroptosis has been elucidated [12][13][14][15][16][17][18]. In this regard, H 2 can be considered a unique molecule that influences fundamental biological responses.…”
Section: Latest Insights Into H 2 Biology Research-brief Summarymentioning
confidence: 99%
“…In this sense, excessive oxidative stress should be suppressed, but the degree of suppression should be at a level that does not compromise the benefits of reactive oxygen species to the body [15]. To date, while many preclinical studies using H 2 have confirmed organ-protective effects and correction of metabolic abnormalities through its antioxidant and anti-inflammatory effects [12][13][14][15][16][17][18], no severe side effects of H 2 loading have been observed. Therefore, the clinical application of antioxidant therapy with H 2 is considered a realistic challenge.…”
Section: H2 Intervention For Ckd and Hemodialysismentioning
confidence: 99%
“…The small size of the hydrogen molecule allows it to easily penetrate the cell membrane to the cytosol. It is naturally metabolized without residue, and therefore, there are no side effects [ 75 ]. Similar to taurine and spermidine, hydrogen has antioxidant [ 76 ], anti-inflammatory, and anti-apoptotic effects [ 77 , 78 ].…”
Section: Managementmentioning
confidence: 99%
“…Because of the small size of the hydrogen molecule, it easily penetrates the cell membrane to the cytosol. Another advantage is that there are no side effects because it can be metabolized without residue [81]. Hydrogen exerts antioxidant [82], anti-inflammatory, and antiapoptotic effects [83,84], which has cardioprotective benefits.…”
Section: Direct Antioxidantsmentioning
confidence: 99%